Balloon-Augmented Leaflet Modification With Bioprosthetic or Native Aortic Scallop Intentional Laceration to Prevent Iatrogenic Coronary Artery Obstruction and Laceration of the Anterior Mitral Leaflet to Prevent Outflow Obstruction: Benchtop Validation and First In-Man Experience. (November 2021) - Perdoncin, Emily; Bruce, Christopher G.; Babaliaros, Vasilis C.; Yildirim, Dursun Korel; Depta, Jeremiah P.; McCabe, James M.; Gleason, Patrick T.; Xie, Joe; Grubb, Kendra J.; Paone, Gaetano; Kohli, Keshav; Kamioka, Norihiko; et al.
Abstract : Background: Bioprosthetic or native aortic scallop intentional laceration to prevent iatrogenic coronary artery obstruction (BASILICA) and laceration of the anterior mitral leaflet to prevent outflow obstruction (LAMPOON) reduce the risk of coronary and left ventricular outflow obstruction obstruction during transcatheter aortic valve replacement and transcatheter mitral valve replacement. Despite successful laceration, BASILICA or LAMPOON may fail to prevent obstruction caused by inadequate leaflet splay in patients having challenging anatomy such as very small valve-to-coronary distance, diffusely calcified, rigid leaflets, or undergoing transcatheter aortic valve replacement inside existing transcatheter aortic valve replacement. We describe a novel technique of balloon-augmented (BA) leaflet laceration to enhance leaflet splay. Methods: We measured the incremental leaflet splay from BA-BASILICA in vitro. From November 2019 to March 2021, 16 patients underwent BA-BASILICA and 4 BA-LAMPOON at 3 centers. Results: BA-BASILICA increased benchtop leaflet tip splay 17%, maximum splay angle 30%, and splay area 23%, resulting in a more rounded apex and larger effective area. Sixteen patients at risk for inadequate BASILICA leaflet splay, including 4 transcatheter aortic valve replacement inside existing transcatheter aortic valve replacement, underwent BA-BASILICA. All had successful leaflet laceration. One had coronary obstruction requiring immediate orthotopic stenting. Two underwent elective orthotopic coronary stenting through the transcatheter valve cells for leaflet prolapse without coronary ischemia. There were no deaths during the procedure or at 30 days. Four patients at risk for inadequate anterior mitral leaflet splay underwent BA-LAMPOON. All had successful target leaflet laceration without left ventricular outflow obstruction obstruction or procedural death. One died within 30 days. Conclusions: BA leaflet laceration enhances leaflet splay in vitro and may allow transcatheter aortic valve replacement and transcatheter mitral valve replacement in patients otherwise ineligible for traditional BASILICA or LAMPOON due to challenging anatomy.